(untitled) (Revista Ciencia Agraria, 2024)
The present work was carried out based on data and zootechnical records from a goat and sheep property in the city of Belo Jardim, Agreste of Pernambuco. With information on three male goats, data were obtained on the pregnant females and those that carried the pregnancy to term, in addition to live births and stillbirths. Based on this data, the Chi-square statistical analysis and Fisher’s test were used to verify the reproductive efficiency of the male goat on the reproductive indices of the females, using the Systat 13 software. The results showed no significant differences between the evaluated males concerning their service capacity, according to the records of a breeding season during the years 2021, 2022, and 2023. This allowed the determination of the percentage of reproductive indices for each male and, with this, to proceed with selecting the most viable breeder for the herd or, if necessary, proceed with disposal. On the other hand, the equal environmental conditions for the males determined that only one showed significant results concerning the reproductive indices of the females. Meanwhile, significant differences were observed between the males during the breeding seasons of 2021 and 2023, but there was a significant effect among the males in the 2022 breeding season (P<0.05). Concluding that the evaluation of reproductive capacity and reproductive indices are important tools in the selection of breeding males.